High Isolated 10-MIMO Antenna Elements for 5G Mobile Applications - Ghawbar, Fayad; Abdul Sukor, Jumadi (International Journal of Integrated Engineering, 2023)
The enormous increase in gadgets has resulted in a data rate shortage insufficient to satisfy the user's needs. The multiple input multiple output (MIMO) technique is substantially deployed in the 5G wireless communication system to increase channel capacity and provide sufficient throughput. However, MIMO antennas are associated with mutual coupling, especially between closely spaced antenna elements, resulting in a low MIMO performance. Therefore, effective isolation techniques are essential to reduce the mutual coupling between the adjacent MIMO antenna elements. A hybrid decoupling technique of self-isolation and an orthogonal mode approach has been proposed to provide significant isolation for high MIMO order 5G mobile applications. A compact self-isolated 10 × 10 MIMO antenna system has been proposed for 5G mobile phone applications operating at the 3.5 GHz frequency band. The antennas act as radiating and isolating elements simultaneously, providing significant isolation. Furthermore, the self-isolated 10-MIMO antenna elements are printed on double side edges of FR-4 small substrates orthogonal to the system substrates, forming an orthogonal mode that enhances the self-decoupling approach. The s-parameters results indicate significant isolation of less than -19 dB between the adjacent 10-MIMO antenna elements. Likewise, the evaluation results of the MIMO performance metrics such as envelope correlation coefficient (ECC), diversity gain (DG), total active reflection coefficient (TARC), and channel capacity Loss (CCL), are less than 0.006, 9.97 dB, -10 dB, and 0.08 bits/s/Hz respectively. The isolation result and the evaluated MIMO performance metrics demonstrate that the proposed 10-MIMO antenna system is sufficient for 5G mobile applications.